Study of Diversity Collembola in Peatlands in Palangka Raya, Central Kalimantan - Awalul Fatiqin; Febri Nur Ngazizah; Yahya Febrianto; Muhammad Sadam Rahmansyah; Fauzan Fikri (Biota, 2023)
The Study of Collembola Diversity in Peatland and Its Role as an Environmental Bioindicator is an exploratory study of the biological diversity in peatland areas. Collembola is a group of insects that have the potential as environmental bioindicators. The research objective was to determine the value of collembola diversity on peatlands. Collembola sampling was carried out by making Pitfall traps and Modified Barlles Funnels. Collembola samples obtained from peatlands were identified and analyzed for index diversity (H'), uniformity (E), and dominance (C) using the Shannon-Wiener formula. The identification results obtained for Collembola were 52 individuals from seven genera at two different locations including Seira sp, Folsomia sp, Lepidoneilla sp, Willowsia sp, Ceratrimeria sp, Paranula sp, and Dicyrtomina sp. Collembola diversity analysis obtained the diversity index (H': 1.75 and H': 1.18) in the moderate category. The uniformity index (E: 0.98 and E: 0.66) is in the high category. While the dominance index (C: 0.20 and C: 0.40) is in a low category. It can be interpreted that peatlands are still in good condition to support the life of other organisms.